Tren Studi Agama di Abad ke-21: Sebuah Kajian Perspektif Muslim Progresif - Sufratman, Sufratman; Karomi, Kholid (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2023)
This paper aims to examine the methods and approaches of religious studies developed by progressive Muslim scholars in Indonesia, namely M. Amin Abdullah. The era of globalization is characterized by an overflow of knowledge, science, and technology, has caused relations between religions, group, cultural and social relations in society to become open and transparet. The problem is that the dynamics of the claim of truth in the cultural sociological sphere have actually strengthened and created tensions dan disharmony in the life of Indonesian society which is pluralistic. Therefore, religious communities in Indonesia, desperately need input from new and fresh models of methodology in the study of religion. Based on the library research, this paper uses descriptive analysis method. The result is the M. Amin Abdullah, has building and developing a new models of methods and approaches in the study of religion, which is called a multidisciplinary approach. The basic assumption of a multidisciplinary approach is that religious sciences cannot limit itself to social sciences and humanities in the globalization era. Therefor, between religious, social sciences, and humanity sciences are to integrated, dialogue, and perfecting one another to solving problems.